2016
DOI: 10.1007/s12298-016-0389-4
|View full text |Cite
|
Sign up to set email alerts
|

A tomato plastidic ATP/ADP transporter gene SlAATP increases starch content in transgenic Arabidopsis

Abstract: A plastidic ATP/ADP transporter (AATP) is responsible for importing ATP from the cytosol into plastids. Increasing the ATP supply is a potential way to facilitate anabolic synthesis in heterotrophic plastids of plants. In this work, a gene encoding the AATP protein, named , was successfully isolated from tomato. Expression of was induced by exogenous sucrose treatment in tomato. The coding region of was cloned into a binary vector under the control of 35S promoter and then transformed into to obtain transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…SSS can be grouped into four types, SSS I, SSS II, SSS III and SSS IV [3][4][5]. A large body of evidence has illustrated that up-regulation of these genes could increase starch accumulation in plants [5,[18][19][20][21][31][32][33][34][35]. In our study, a significant increase of SSS activity was also observed in transgenic plants ( Figure 5).…”
Section: Up-regulated Starch Biosynthetic Genes and Increased Enzyme supporting
confidence: 71%
See 1 more Smart Citation
“…SSS can be grouped into four types, SSS I, SSS II, SSS III and SSS IV [3][4][5]. A large body of evidence has illustrated that up-regulation of these genes could increase starch accumulation in plants [5,[18][19][20][21][31][32][33][34][35]. In our study, a significant increase of SSS activity was also observed in transgenic plants ( Figure 5).…”
Section: Up-regulated Starch Biosynthetic Genes and Increased Enzyme supporting
confidence: 71%
“…Heterologous expression of SnRK1 from apple/sweet potato increases the starch content in transgenic tomato/tobacco plants [17,18]. Arabidopsis thaliana plants expressing AATP CONTACT Feibing Wang wangfeibing1986@163.com; wangfeibing@hyit.edu.cn from tomato/potato exhibit higher starch content [19,20]. Overexpression of IbAATP increases the starch and amylose content in transgenic sweet potato [21].…”
Section: Introductionmentioning
confidence: 99%
“…There a few reports that the AATP gene has been shown to be involved in starch accumulation in plants [17][18][19][20][21][22]. In this work, the VvAATP gene was isolated from grapevine.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of VvAATP and starch biosynthesis related genes was analyzed by real-time quantitative PCR (qRT-PCR) as described by Wang et al [19]. The cDNA solution was used as templates for PCR amplification with gene specific primers ( Table 1).…”
Section: Expression Analysis Of the Related Genesmentioning
confidence: 99%
See 1 more Smart Citation